Impact of human potential quality indicators on the regional economy development - E. A. Ostapenko (Управление)
The article provides an assessment of the quality of human potential, which includes the use of the most effective indicator, on the basis of which it is possible to analyze the standard of living of citizens - the human development index, in relation to the constituent entities of the Russian Federation. In the course of the analysis, priority directions for the development of the constituent entities of the Russian Federation were identified and regularities were determined. The elements on the basis of which one can judge the quality of human potential in modern economic and social conditions are considered and defined. The purpose of the study is to analyze and evaluate the relationship between the components of the quality of human potential and development indicators of the constituent entities of the Russian Federation. The objectives of the study are to form an assessment of the quality of human potential in the context of the regional economy, using the HDI indicator. In the course of the study, methods of a general scientific and special nature were used: analysis, synthesis, abstraction, induction and deduction. In the course of the study, it was possible to form a model consisting of several indicators, on the basis of which a conclusion was made about the existing level of human potential of citizens of the Russian Federation. The practical significance of the study lies in the possibility of using its results in shaping the development paths of the regions of the Russian Federation.